Red Star Over Birobidzhan: Canadian Jewish Communists and the "Jewish Autonomous Region" in the Soviet Union - Srebrnik, Henry (Labour / Le Travail, 1999)
Chronicles the work of the Organization for Jewish Colonization in Russia (ICOR) during the 1920s and 30s in support of a Soviet government initiative that established a Jewish Autonomous Region in Birobidzhan in the far east of the Soviet Union. ICOR was also founded in opposition to the Zionist movement for a Jewish national state in Palestine. Controlled by the US and Canadian communist parties, the organization was comprised mostly of Yiddish-speaking East European Jews. In 1933, ICOR claimed a membership of 10,000 members including a Canadian section with members in 10 cities in four provinces. The Canadian section also published a periodical, "Kanader Icor." Concludes that the project for a Jewish Autonomous Region was a largely fraudulent scheme that unravelled under the weight of the Stalinist purges in the Soviet Union as well as developments in the international sphere.